2016
DOI: 10.1103/physrevd.94.044006
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of deformed black holes. I. Majumdar-Papapetrou binary

Abstract: Although black holes are eminent manifestations of very strong gravity, the geometry of spacetime around and even inside them can be significantly affected by additional bodies present in their surroundings. We study such an influence within static and axially symmetric (electro-)vacuum space-times described by exact solutions of Einstein's equations, considering astrophysically motivated configurations (such as black holes surrounded by rings) as well as those of pure academic interest (such as specifically "… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…The properties of some associated curvature as well as electromagnetic invariants have been recently studied in Ref. [24].…”
Section: The Majumdar-papapetrou Solutionmentioning
confidence: 99%
“…The properties of some associated curvature as well as electromagnetic invariants have been recently studied in Ref. [24].…”
Section: The Majumdar-papapetrou Solutionmentioning
confidence: 99%
“…With the aim to study the geometry of black holes surrounded by other strong sources of gravity, we first [1] considered the Majumdar-Papapetrou binary made of two extremely charged black holes and found that the horizon interior is not much deformed within this class of solutions. Therefore, in the second paper [2], we tried to distort a black hole which is far from being extreme (actually the Schwarzschild one), surrounding it by a concentric static and axisymmetric thin ring (described by the aged Bach-Weyl solution).…”
Section: Introductionmentioning
confidence: 99%
“…In such coordinates, the metric reads ds 2 = −N 2 dt 2 + ρ 2 N 2 dφ 2 + e 2λ N 2 dρ 2 + dz 2 and only contains two unknown functions N ≡ e ν and λ of ρ and z, of which ν, representing the Newtonian potential, is given by solution of Laplace equation, so it superposes linearly when the field of multiple sources is being seeked. 1 For the Weyl-type metric, the above invariants N , κ and K are given by…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two-hole MP spacetime can also be obtained as the extreme limit of the double RN solution [7]. Recently, MP spacetimes were used to study the influence of external sources on black holes since one expects that the most powerful effect is to be expected from an additional black hole [8].…”
Section: Introductionmentioning
confidence: 99%